2006
DOI: 10.1108/09540910610665071
|View full text |Cite
|
Sign up to set email alerts
|

Coffin‐Manson constant determination for a Sn‐8Zn‐3Bi lead‐free solder joint

Abstract: Purpose -To determine the Coffin-Manson (CM) equation constants for fatigue life estimation of Sn-8Zn-3Bi solder joints, since Sn-8Zn-3Bi solder has a melting temperature of around 1998C which is close to that of the conventional Sn-Pb solder which has previously been used in the electronics assembly industry. Design/methodology/approach -Three dimensional finite element (FE) simulation analysis was used for comparison with the experimentally measured data and to determine the CM constants. Low cycle fatigue t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Thus, the intermetallics could be identified as (Cu,Ni) 6 Sn 5 . According to Sun et al 21 in binary Cu 6 Sn 5 IMCs, the atomic percentage of Sn is around 45. Moreover, the difference in atomic size between Ni and Cu is only 2 and both the elements have same FCC lattice structure, the addition of Ni into Cu 6 Sn 5 without causing lattice distortion or a new phase formation is possible.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the intermetallics could be identified as (Cu,Ni) 6 Sn 5 . According to Sun et al 21 in binary Cu 6 Sn 5 IMCs, the atomic percentage of Sn is around 45. Moreover, the difference in atomic size between Ni and Cu is only 2 and both the elements have same FCC lattice structure, the addition of Ni into Cu 6 Sn 5 without causing lattice distortion or a new phase formation is possible.…”
Section: Resultsmentioning
confidence: 97%
“…to have longer fatigue life than Sn-37Pb at room temperature [22,23]. Solomon et al [31] found that the IF resistance of both eutectic Sn-Ag and Sn-40Pb single lap joints decrease with increasing the temperature and the fatigue life of lead-free solder joints to be longer than that of leaded solder joints at both 35°C and 150°C.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the symmetry of triangular waves had no significant effect on crack initiation or life for lead-free micro specimens, in contrast to the reductions observed for large size specimens. Peng et al [22,23] determined the Coffin-Manson constants for the low cycle fatigue life of Sn-8Zn-3Bi solder joints, using Sn-37Pb eutectic as a reference. Duek et al [24] carried out low cycle isothermal fatigue tests on 96.5Sn-3.0Ag-0.5Cu solder joints at 24°C, 30°C, 60°C, 100°C, and 125°C with fixed constant displacement amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…If the cycles have sufficient half-cycle dwell times to result in complete stress-relaxation/creep, then ∆D = ∆W. Englemaier has suggested that the fatigue ductility exponent is a function of temperature and time: [172] 0.37 63Sn-37Pb Anderson, et al [97] 0.42 SAC Lee, et al [98] 0.43 Sn-Cu Kariya, et al [173] 0.44 SAC Lee, et al [98] 0.57 Sn-Ag Akay, et al [165] 0.63 SAC Wu, et al [166] 0.68 SAC Lee, et al [98] 0.74 SAC Lee, et al [94] 0.87 Sn-Ag-Bi Pang, et al [174] 0.99 Sn-Cu Kanchanomai, et al [176] 1.14 Sn-Ag-Cu-Bi [91] 0.37 Sn-Pb Anderson, et al [100] 0.42 SAC Kanda, et al [91] 0.49 SAC Lau, et al [100] 0.51 SAC Akay, et al [165] 0.63 SAC Wu, et al [166] 0.68 SAC Shi, et al [70] 0.70 Sn-Pb Pang, et al [101] 0.87 SAC0387 Kim, et al [92] 0.88 SAC405 Ahmer, et al [167] 1.00 SAC Jung, et al [168] 1.00 63Sn37Pb Dudek, et al [169] 1.00 SAC Pang, et al [170] 1.07 SAC at 25C Chi, et al [171] 1.10 SAC Lee, et al [98] 1.17 Sn3.5Ag7.5Bi…”
Section: Fatigue Life Predictionmentioning
confidence: 99%